Association of Paraoxonase 1 Gene Polymorphism and Enzyme Activity With Carotid Plaque in Rheumatoid Arthritis. Issue 11 (28th October 2013) - Charles‐Schoeman, Christina; Lee, Yuen Yin; Shahbazian, Ani; Gorn, Alan H.; FitzGerald, John; Ranganath, Veena K.; Taylor, Mihaela; Ragavendra, Nagesh; McMahon, Maureen; Elashoff, David; Reddy, Srinivasa T.
<x xml:space="preserve">Abstract</x> Objective To investigate the relationship of genetic and biochemical determinants of paraoxonase 1 activity to carotid plaque as a surrogate marker of cardiovascular (CV) risk in patients with rheumatoid arthritis (RA). Methods The relationships between paraoxonase 1 activity, PON1 genotype (for the functional polymorphism at position 192), and carotid plaque presence were determined in 168 RA patients. After an overnight fast, blood was collected for lipoprotein analysis, and paraoxonase 1 activity was measured using paraoxon as the substrate. The PON1 Q192R genotype was determined for all patients. Lipoprotein cholesterol levels, traditional CV risk factors, medication use, and RA disease characteristics were assessed for all patients. Results Paraoxonase 1 activity values in the RA patients were highest for the RR genotype, intermediate for the QR genotype, and lowest for the QQ genotype (P < 0.0001). Compared to patients with either the QQ genotype or the QR genotype, patients with the RR genotype demonstrated decreased risk of carotid plaque on multivariate analysis, controlling for traditional CV risk factors, high‐sensitivity C‐reactive protein levels, prednisone use, and cholesterol‐lowering medication use (P < 0.05). Additional multivariate logistic regression analysis controlling for the above factors also revealed a significant association of plasma paraoxonase 1 activity with carotid plaque in RA patients. Lower plasma paraoxonase 1 activity was associated with increased risk of carotid plaque (P < 0.05). Conclusion The current findings suggest a relationship of the genetic determinants and activity of paraoxonase 1 to CV risk in RA patients, as assessed by the presence or absence of carotid plaque. Further CV outcome studies are warranted to validate the utility of paraoxonase 1 as a biomarker of CV risk in patients with RA.